Are data available for tracking progress on nutrition policies, programs, and outcomes in Afghanistan? - Jangid, Manita; Neupane, Sumanta; Scott, Samuel P.; Nguyen, Phuong Hong; Kim, Sunny S.; Murira, Zivai; Torlesse, Harriet; Menon, Purnima (International Food Policy Research Institute, 2021)
The World Health Organization (WHO) and other global nutrition and health agencies recommend nutrition actions throughout the life-course to address malnutrition in all its forms. In this report, we examined how Afghanistan’s nutrition policies and programs address recommended nutrition actions, determinants, and outcomes. We reviewed population-based surveys to assess the availability of data on nutrition actions, nutrition outcomes, and the determinants of these outcomes; we also assessed the data availability in administrative data systems for selected nutrition actions and outcomes. Our review identified a total of 53 recommended evidence-based nutrition actions; of these, 50 were applicable to Afghanistan, and 44 of those were addressed in nutrition policies and programs. Nutrition actions that were not included in current policies and programs were: food supplementation during adolescence, food supplementation for complementary feeding, and iron and folic acid (IFA) supplementation during childhood. Although policies addressed IFA supplementation and deworming during preconception and calcium supplementation during pregnancy, there was currently no program to implement these actions. National strategies and plans recognized and aimed to address all key determinants of nutrition; they also expressed an intent to address all Sustainable Development Goal (SDG) nutrition targets for maternal, infant, and young child nutrition. Noncommunicable diseases (NCDs), however, did not currently have targets in the national strategies. Of the 44 actions that Afghanistan’s policies and programs address, our data review indicated that population-based surveys contained data on only 22 actions; similarly, out of 17 selected actions we reviewed in the administrative data system, data was available on only ten actions. In population-based surveys, data was not available on indicators related to IFA supplementation and deworming during adolescence, counseling during pregnancy, newborn care, counseling on infant and young child feeding (IYCF), or on growth monitoring, identification and management of severe acute malnutrition (SAM) and moderate acute malnutrition (MAM) during early childhood. In administrative data systems, data was not available on IFA supplementation and counseling during pregnancy, support for early initiation of breastfeeding, multiple micronutrient powder (MNP), or zinc supplementation during early childhood. Most indicators on immediate and underlying determinants were available from population-based surveys; however, none of the population-based surveys contained data on dietary diversity among pregnant women or coverage of households under the social protection schemes. Data on all outcome indicators were available in the population-based surveys. In conclusion, Afghanistan’s landscape for nutrition is robust but its consideration of NCDs is limited. The gaps in data availability for tracking progress on nutrition are much greater than the gaps in the policies and programs that are designed to address the recommended actions. Future population-based surveys and other data systems should aim to fill the identified data gaps for nutrition actions.